Nasal Analysis and Anatomy: Anthropometric Proportional Assessment in Asians—Aesthetic Balance from Forehead to Chin, Part I - Suhk, JeongHoon (Semin Plast Surg, 2015)
Asian rhinoplasty patients can be analyzed by the nose's component structures and their relationship to one another. A comprehensive understanding of the underlying anatomical structure including bone, cartilage, and soft tissue contributes to better preoperative planning. To achieve an optimal postoperative result, a thorough preoperative analysis utilizing standardized measurements is essential. Knowledge of the Asian nose facilitates the use of an algorithmic approach to Asian rhinoplasty that increases surgical predictability.